Огляд та перспективи розвитку матеріалів для контактів електромеханічних апаратів низької напруги - Клименко, Борис Володимирович; Кохановський, Василь Олександрович (НТУ "ХПІ", 2011)
Розглянуто особливості матеріалів для контактів терміналів, властивості та склад композитних матеріалів для контактних елементів комутаційних апаратів. Наводяться дані щодо нового композитного контактного матеріалу

The characteristics of materials for contact terminals, as well as the properties and composition of composite materials in the contact elements of the most common types of electromechanical switching devices. Privat-dyatsya data on the new wear resistant and environmentally safe composite contact material
Review and prospects of materials for contacts electric equipment low voltage
Keywords: провідники; ручне керування; електромеханіка; запобіжники; contact elements; electromechanical switching devices; composite; characteristics of materials